2019
DOI: 10.3390/math7111070
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution of Sloshing in a Cylindrical Tank with an Elastic Cover

Abstract: Coupled fluid-structure is significant in many aspects of engineering applications such as aerospace fuel tanks, the seismic safety of storage tanks and tuned liquid dampers. Numerical investigation of the effects of thin plate cover over a cylindrical rigid fuel tank filled by an inviscid, irrotational, and incompressible fluid is investigated. Governing equations of fluid motion coupled by plate vibration are solved analytically. A parameter study on the natural frequency of coupled fluid-structure interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They observed that two or three vertical baffles could minimize the sloshing impact to a great extent. Jamalabadi investigated the effects of covering a rigid, cylindrical fuel tank with a thin plate [17]. He studied the fundamental angular velocity of linked fluidstructure motion as a parameter.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that two or three vertical baffles could minimize the sloshing impact to a great extent. Jamalabadi investigated the effects of covering a rigid, cylindrical fuel tank with a thin plate [17]. He studied the fundamental angular velocity of linked fluidstructure motion as a parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [36] and Sun et al [37] performed classical nonlinear works on sloshing while the nonlinearity refers to the fluid part. Jamalabadi [38,39] solved the FSI problem in analytical sloshing, sloshing with the improved boundary layer approximation [40], sloshing with finite element [41,42], LBM [43], and sloshing with SPH method [44]. In many of studies a linear elastic model is adopted for solid part and focus of accuracy is on fluid section [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Tank materials properties have been treated in [11], [12], [13], [14], [15], [16], [17]. The different partition types' effect on the frequencies and tank oscillations amplitudes has been presented in works, [18], [19], [20], [21]. Forced tank oscillations with partially filled liquid have been studied in [22], [23], [24], [25].…”
Section: Introductionmentioning
confidence: 99%